PENGARUH KOMPETENSI, KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. ALNS ANGLO EASTERN INDONESIA DI JAKARTA - Enjang Sudarman; Fathan Anas (Sekolah Tinggi Manajemen IMMI Jakarta, 2020)
This study aims to look at the Effect of Competence, Compensation and Motivation on Employee Performance at PT. ALNS Anglo Eastern Indonesia in Jakarta. The study population was 161 employees. The research sample was taken by census. The technique of collecting data using a questionnaire. Data analysis using correlation and multiple linear regression techniques. Based on the results of the analysis show that competence, compensation and motivation have a positive effect on performance with a regression coefficient constant value of 39.781.Based on the results of calculations with the SPSS version 21 program, it was found that the R2 results were 0.549 or 54.9%, this means that 54.9% of the variables in employee performance were influenced by competence, compensation and motivation, while the remaining 45.1% was influenced by variables other. The results of the analysis also show that statistically, competency factors, compensation and motivation of the three variables in this study simultaneously and partially have an influence on the high and low performance of PT. ALNS Jakarta.Based on the results of this study, it turns out that competency factors, compensation and motivation can shape performance in the PT. Jakarta ALNS is good so that it can achieve the goals of organizational success effectively and efficiently.